2018
DOI: 10.18632/oncotarget.24064
|View full text |Cite
|
Sign up to set email alerts
|

The association between BRCA1 gene polymorphism and cancer risk: a meta-analysis

Abstract: Many studies have reported that BRCA1 polymorphisms are associated with cancer risk, but the results remain controversial. The purpose of this meta-analysis is to evaluate the relationship between BRCA1 polymorphisms (rs799917, rs1799950, rs1799966, or rs16941) and cancer risk. Relevant studies were identified via a systematic search of the PubMed, Embase, and Web of Science databases up to July 31, 2017. Odds ratios (ORs) with 95% confidence intervals (CIs) were calculated to examine the strength of the assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 47 publications
1
19
0
2
Order By: Relevance
“…However, when dealing with cancers as subgroups, they found that among Asian populations, the rs799917 polymorphism is associated with decreased risk of esophageal squamous carcinoma, gastric carcinoma, cervical cancer, and non-Hodgkin lymphoma. 51 This study is the first to address the relationship between BRCA1 rs1799966 and rs799917 SNP, and the risk of GBM among the Arab Jordanian population. The findings of the study show that BRCA1 rs799917 is associated with decreased risk of GBM in the recessive model (AA vs G/ G-A/G: OR, 0.46, 95% CI, 0.26-0.82, p=0.01) and the same SNP is associated with increased risk of GBM in the overdominant model (AG vs G/G-A/A: OR, 1.72, 95% CI, 1.02--2.89, p=0.04).…”
Section: Dovepressmentioning
confidence: 99%
“…However, when dealing with cancers as subgroups, they found that among Asian populations, the rs799917 polymorphism is associated with decreased risk of esophageal squamous carcinoma, gastric carcinoma, cervical cancer, and non-Hodgkin lymphoma. 51 This study is the first to address the relationship between BRCA1 rs1799966 and rs799917 SNP, and the risk of GBM among the Arab Jordanian population. The findings of the study show that BRCA1 rs799917 is associated with decreased risk of GBM in the recessive model (AA vs G/ G-A/G: OR, 0.46, 95% CI, 0.26-0.82, p=0.01) and the same SNP is associated with increased risk of GBM in the overdominant model (AG vs G/G-A/A: OR, 1.72, 95% CI, 1.02--2.89, p=0.04).…”
Section: Dovepressmentioning
confidence: 99%
“…The wild type genotype (CC) was associated with increased risk of gastric cancer (Wang et al, 2015), esophageal squamous cell carcinoma (ESCC) (Zhang et al, 2013) and non-Hodgkin Lymphoma (NHL) (Chen et al, 2013), but not associated with thyroid carcinoma (Xu et al, 2012) and ovarian cancer (Wenham et al, 2003;Auranen et al, 2005). In a recent meta-analysis (Xu et al, 2018), the p.Pro871Leu polymorphism was linked to decreased risk of various cancers like ESCC, cervical cancer, gastric cancer and NHL among Asians. But some studies from Chinese populations have reported significant associations between the BRCA1 p.Pro871Leu variant and breast cancer, where the CT genotype provides increased risk to breast cancer in these populations (Huo et al, 2009;Wang et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Genomic DNA was extracted from peripheral blood lymphocytes by a standard phenol-chloroform method (Adeli and Ogbonna, 1990). Four variants of BRCA1, c.190T>C (p.Cys64Arg), 1307delT, g.5331G>A (p.G1738R) and c.2612C>T (p.Pro871Leu) were screened by a PCR-RFLP method using published primer sequences (Gajalakshmi et al, 2007;Karami and Mehdipour, 2013;Xu et al, 2018).…”
Section: Dna Isolation and Screening Of Brca1 Variantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Table 1 (Tab. 1) (References in Table 1: Chang et al, 2014[ 1 ]; Chen et al, 2015[ 2 ]; Cheng et al, 2015[ 3 ]; Dai et al, 2015[ 4 ]; Deng et al, 2014[ 5 ]; Gong et al, 2016[ 9 ]; Han et al, 2012[ 11 ]; He et al, 2013[ 12 ]; Hua et al, 2014[ 14 ]; Jia et al, 2017[ 16 ]; Kuang et al, 2014[ 17 ]; Li et al, 2015[ 20 ]; Li et al, 2016[ 18 ]; Li et al, 2017[ 19 ]; Liang et al, 2018[ 21 ]; Liu et al, 2011[ 23 ]; Liu et al, 2011[ 24 ]; Liu et al, 2014[ 25 ]; Liu et al, 2014[ 26 ]; Lu et al, 2012[ 27 ]; Ma et al, 2013[ 29 ]; Ma et al, 2013[ 30 ]; Ma et al, 2017[ 28 ]; Mo et al, 2016[ 31 ]; Mocellin et al, 2015[ 32 ]; Namazi et al, 2018[ 35 ]; Pabalan et al, 2015[ 36 ]; Peng and Xu, 2015[ 37 ]; Qi et al, 2016[ 38 ]; Qin et al, 2017[ 39 ]; Ribeiro et al, 2017[ 41 ]; Shen et al, 2014[ 47 ]; Shi et al, 2014[ 48 ]; Shi et al, 2017[ 49 ]; Shi et al, 2018[ 50 ]; Tian et al, 2012[ 52 ]; Wang et al, 2013[ 53 ]; Wang et al, 2014[ 54 ]; Wang et al, 2015[ 56 ]; Wang et al, 2015[ 57 ]; Wang et al, 2016[ 55 ]; Wu et al, 2015[ 58 ]; Xie et al, 2017[ 59 ]; Xu et al, 2014[ 61 ]; Xu et al, 2014[ 63 ]; Xu et al, 2015[ 62 ]; Xu et al, 2018[ 60 ]; Yadav et al, 2018[ 64 ]; Yan et al, 2013[ 65 ]; Yang et al, 2014[ 66 ]; Yang et al, 2016[ 67 ]; Ye et al, 2017[ 68 ]; Yu et al, 2014[ 69 ]; Zhang et al, 2012[ 72 ]; Zhang et al, 2013[ 71 ]; Zhang et al, 2015[ 74 ]; Zhang et al,...…”
mentioning
confidence: 99%